CircRNA expression profile of bovine placentas in late gestation with aberrant SCNT fetus. Issue 6 (26th May 2019) - Su, Xiaohu; Gao, Guangqi; Wang, Shenyuan; Su, Guanghua; Zheng, Zhong; Zhang, Jiaqi; Han, Lidong; Ling, Yu; Wang, Xiuying; Li, Guangpeng; Zhang, Li
Abstract: Backgrounds: One of the limitations of somatic cell nuclear transfer (SCNT) strategy to generate genetically modified offspring is the low birth rate. Placental dysfunction is one of the causes of abortion. Circular RNA (circRNA) is noncoding RNA which functions as microRNA (miRNA) sponges in biological processes. Methods: Two aberrant pregnant placenta (aberrant group, AG) and three normal pregnant placenta (normal group, NG) during late gestation (180‐210 days) with bovine SCNT fetus were collected for high‐throughput sequencing and analyzed. The host genes of differentially expressed (DE) circRNAs were predicted. And the microRNAs (miRNAs) which could interact with DE circRNAs were analyzed. Then, the expressional level of partial DE circRNAs and corresponding host genes was verified through qRT‐PCR. At last, the function of host genes was analyzed through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Results: Altogether 123 differentially expressed circRNAs between two groups were identified, which were found related to 60 host genes and 32 miRNAs. The top 10 upregulated circRNAs were bta_circ_0012985, bta_circ_0013071, bta_circ_0013074, bta_circ_0016024, bta_circ_0013068, bta_circ_0008816, bta_circ_0012982, bta_circ_0013072, bta_circ_0019285, and bta_circ_0013067. The top 10 downregulated circRNAs were bta_circ_0024234, bta_circ_0017528, bta_circ_0008077, bta_circ_0003222, bta_circ_0007500, bta_circ_0020328, bta_circ_0011001, bta_circ_0016364, bta_circ_0008839, and bta_circ_0016049. The qRT‐PCR results showed consistent trend with sequencing analysis result, while host genes had no statistic difference. The GO and KEGG analyses of the host genes suggested that abnormal circRNA expression may play multiple roles in placental structure and dysfunction. Conclusion: The abnormal circRNA expression may be one of reasons of placental dysfunction, leads to abortion of bovine SCNT fetus.